Dihotomy of Law: Historical Analysis, Current Trends, a Combination of Private and Public Principles in Civil Law - M. V. Tregubov (Теоретическая и прикладная юриспруденция)
The article is devoted to the perception of private and public law in the tradition of the Romano-German legal family. With the use of formal-logical, sociological-legal and retrospective methods of research the author studies the transformation of views on the grounds of differentiation of private and public law, analyzes the current trends in the development of scientific thought on the problem of dichotomy of law, the combination of private and public principles in civil law is studied. The conclusion is made about the development of two interrelated processes in the modern legal systems of Russia and Europe — “publicization” of private law and “commercialization” of public law.